Methane decomposition on Ni-Cu alloyed Raney-type catalysts - A. F. Cunha (2009)
In the present work, we report on the performance of Ni-Cu alloyed Raney-type catalysts for the production of hydrogen by catalytic methane decomposition. The activity of the catalysts was assessed by comparing the experimental conversions with the calculated equilibrium conversions for each set of experimental conditions. The stability of the catalysts was assessed by comparing the maximum conversions with the conversions at the end of 5 h tests. Comparison with monometallic Ni Raney-type catalytic systems shows that Cu addition significantly improves catalyst stability. Excellent results were obtained when the Ni-Cu Raney-type system was thermally treated in situ at 600 degrees C, as a result of incipient alloy formation.